Notes on a Newly Discovered Draft of the Poem 'Le Petit Sot'. Issue 2 (September 2017) - Van Hulle, Dirk; Verhulst, Pim
Abstract : During our work on the transcription of the manuscript notebooks of Malone meurt for the Beckett Digital Manuscript Project, we recently discovered a draft of the poem 'Le Petit Sot' which, to the best of our knowledge, was so far unknown to Beckett scholars. In this article, we situate the draft in its material and chronological context, and relate these findings to the authorship debate surrounding Beckett's 'Petit Sot' poems. In doing so, we argue that it contributes to the emergence of a pattern towards stylistic simplification and ignorance in his work, which can be traced from the French poems he started writing at the end of the 1930s, to late works such as the mirlitonnades, Stirrings Still and 'comment dire' / 'what is the word'. As a consequence, what Beckett once referred to as his post-war 'revelation' might better be conceived of as a gradual, bilingual process rather than a sudden epiphany.